Characterizing CO2 plume migration in multi-layer reservoirs with strong heterogeneity and low permeability using time-lapse 2D VSP technology and numerical simulation. (January 2020) - Diao, Yujie; Zhu, Guowei; Li, Xufeng; Bai, Bing; Li, Jun; Wang, Yongsheng; Zhao, Xinglei; Zhang, Bing
Highlights: The time-lapse 2D vertical seismic profiling (VSP) technology can support the monitoring and numerical modeling of CO2 plume migration at the CO2 geological storage site. Results of time-lapse VSP data and numerical modeling show some new characteristics of CO2 plume migration in multi-layer reservoirs with strong heterogeneity and low permeability. A new 3D geological model of Shenhua CCS demonstration project in China is constructed. Characteristics of CO2 plume migration during the injection period and after site closure at the Shenhua CCS demonstration project storage site are much clearer than previous studies. Abstract: One of the great challenges in carbon capture and storage (CCS) development is the monitoring and determination of the underground CO2 plume migration. We show that time-lapse 2D vertical seismic profiling (VSP) technology can support the monitoring and numerical modeling of CO2 plume migration at a storage site. Using the Shenhua CCS demonstration project in China as a case study, we predicted the physical parameters of the main reservoir, including the distribution of bodies of sandstone and their porosity and permeability, required to upgrade the geological model. We also interpreted the characteristics of historical CO2 plume migration in one seismic profile of the second and third periods of VSP monitoring. Based on a new upgraded geological model, we simulated the historical CO2 plume migration characteristics under the actual injection scenario of the demonstration project. The results of the simulation exhibited good consistency with the time-lapse VSP monitored in the profile, thus indicating that both the geological and numerical models have a certain degree of credibility. We further simulated the characteristics of CO2 plume migration after the injection well shutoff before 2035.